Climbing out of a software black hole. (28th March 2021) - Carter, Lynn Robert
Abstract: As we become ever more dependent on computer systems for much of what we do, we are losing the battle with cyber criminals and suffer from poor‐quality offerings. Mission‐critical, life‐critical, and infrastructure‐critical systems should be secure, reliable, and worthy of trust. Yet, that is not our experience. Many firms complain that entry‐level software workers do not have the skills and abilities to do what is required and yet we continue to teach computer science in ways very similar to what we did in the 1970s and '80s. As we spiral downward, it's hard to know precisely where the event horizon might be, so let us deal with it now. It's time for an educational and societal sea change when it comes to computing. Society has demonstrated the willingness to deal with such issues in medicine and other critical domains. Highly‐skilled clinical professors teach new physicians and specialists using the processes, methods, tools, and disciplines learners are expected to use as practicing professionals. It is time for the crucial software domains to leverage these proven methods and stop pushing off to employers these critical aspects of what it means to be a software professional.